Involvement of a Response Regulator VdSsk1 in Stress Response, Melanin Biosynthesis and Full Virulence in Verticillium dahliae - Zheng, Jiayue; Tang, Chen; Deng, Chenglin; Wang, Yonglin (Frontiers in Microbiology, 2019)
Verticillium dahliae causes devastating diseases on over 200 plant species worldwide. This fungus forms melanized microsclerotia which help it to survive under adverse conditions and are vital to the disease spread. Here, we identified and characterized a V. dahliae homolog to Ssk1, a response regulator of the two-component system in Saccharomyces cerevisiae. The VdSsk1 deletion strains are more sensitive to various stresses including H2O2 and sodium nitroprusside dihydrate, while the mutants confer higher resistance to fungicides such as fludioxonil and iprodione. Furthermore, disruption of VdSsk1 results in significant downregulation of melanin biosynthesis-related genes, but not affect microsclerotial development. Phosphorylation of VdHog1 is not detected in the VdSsk1 deletion strains under the treatment of sorbitol, indicating that phosphorylation of VdHog1 is dependent on VdSsk1. Finally, we demonstrated that VdSsk1 is required for full virulence. Taken together, this study suggests that VdSsk1 modulates stress response, melanin biosynthesis and virulence of V. dahliae.